2010
DOI: 10.5194/angeo-28-233-2010
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of counter-streaming solar wind suprathermal electrons at solar minimum: STEREO observations

Abstract: Abstract.Previous work has shown that solar wind suprathermal electrons can display a number of features in terms of their anisotropy. Of importance is the occurrence of counter-streaming electron patterns, i.e., with "beams" both parallel and anti-parallel to the local magnetic field, which is believed to shed light on the heliospheric magnetic field topology. In the present study, we use STEREO data to obtain the statistical properties of counter-streaming suprathermal electrons (CSEs) in the vicinity of cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 55 publications
5
28
1
Order By: Relevance
“…1f). The appearence of counter-streaming suprathermal electrons strongly supports the idea of its origin in conjunction with a CIR, as was observed by Lavraud et al (2010). These low-energy electrons may be accelerated or/and reflected at the CIR.…”
Section: Possible Source Of Ami Eventsupporting
confidence: 60%
“…1f). The appearence of counter-streaming suprathermal electrons strongly supports the idea of its origin in conjunction with a CIR, as was observed by Lavraud et al (2010). These low-energy electrons may be accelerated or/and reflected at the CIR.…”
Section: Possible Source Of Ami Eventsupporting
confidence: 60%
“…By analyzing MCs we can therefore analyze the properties of magnetic loops which have emerged near active regions. Owing to their large velocities, suprathermal electrons propagating parallel (or anti-parallel) to the magnetic field constitute tracers of the heliospheric magnetic topology (see, e.g., Zwickl et al, 1983;Lavraud et al, 2010) and enable us to study the connectivity of MCs at the Sun. Observation of counter-streaming, bi-directional strahl populations is interpreted as the signature of magnetic field lines with both ends connected to the Sun (see, e.g., Pilipp et al, 1987;Lavraud et al, 2009), and is often thought of as a magnetic cloud identifier (Gosling et al, 1987).…”
Section: Basic Observational Factsmentioning
confidence: 99%
“…We analyzed the pitch angle spectrograms in the heat energy range of approximately 80 eV to 300 eV to determine the CSEs within the SIMFRs. The CSE events were confirmed through their pitch angle distributions that show higher phase space densities in the field‐aligned and antifield‐aligned directions as compared with the perpendicular (90° pitch angle) direction [ Lavraud et al , ]. The identification of CSE boundaries is important to calculate the percentages of CSEs coincident with the SIMFRs.…”
Section: Observationsmentioning
confidence: 99%
“…Many observations revealed that counterstreaming suprathermal electrons (CSEs) were one of the characteristics used to identify MCs, and they can be interpreted as signatures of closed magnetic field lines, with both ends connected to the Sun [ Gosling et al , ; Bothmer et al , ; Larson et al , ; Shodhan et al , ; Crooker et al , , ]. CSEs can also be produced by other mechanisms, e.g., connection to the Earth's bow shock [ Feldman et al , ; Stansberry et al , ] and distribution function depletions near the 90° pitch angle [ Gosling et al , , ; Skoug et al , ], CSEs are also frequently observed inside or outside CIRs [ Steinberg et al , ; Lavraud et al , ]. If SIMFRs are the interplanetary manifestations of CMEs produced in the solar corona, and some SIMFRs, like MCs, may still be attached to the Sun at both ends, then these SIMFRs should contain CSEs.…”
Section: Introductionmentioning
confidence: 99%